Training and Use of Contemporary Music by Conservatory Teachers in Spain (Música Hodie, 2024)
The aim of this study is to investigate the knowledge, training and use of contemporary music by teachers at different conservatories in Spain. The objectives arise from the need to analyze the reason why contemporary music is not taught uniformly in the different conservatories and to ask about the use made by teachers. To this end, research has been designed with 113 participants who form part of this conservatory teaching staff and who responded to an ad hoc questionnaire. The results show how teachers consider themselves poorly trained and therefore barely address this content. Correlations are found between teachers' training in how to approach contemporary music and their use of it in the conservatory classroom. This data provides some answers to the issues and questions that should be explored further to find solutions and improve in this area. Contemporary music is a part of our daily lives and its study allows for comprehensive development of current students, with conservatories being a key place to carry out this type of research.